Pengaruh Leguminosa Cover Crop (LCC) MucunaBracteatapada Tiga Kemiringan Lahan Terhadap Sifat Kimia Tanah dan Perkembangan Akar Kelapa Sawit Belum Menghasilkan - Ariyan Saputra; Wawan Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the effect of using LCC Mucuna bracteataon three of land slope to soil chemical properties and root growth of immature oil palms. This research conducted in PTPN V Unit Lubuk Dalam, Siak and analysis of soil chemistry in the soil Laboratory Faculty of Agriculture University of Riau. This research conductedjanuary to june 2016. The research used split plot design. The level of land slope (K) as the main plot consists of: K1 = slope 2%, K2 = 7%, K3 = 13%. Mucuna bracteata(M) as the subplot consist of: M0 = cleaned Mucuna bracteata and M1 = overgrown Mucuna bracteata. The variabels observed were soil pH, organic-C, total-N, total-P, total-K, cation excharge capacity, base saturation, root dry weight, root volume and root occupy. The results showed: (1) the interaction between slope level and used of Mucuna bracteatadid not effect all parameters of soil chemical properties and root growth; (2) at the overgrown LCC Mucuna bracteata, soil pH, organic-C, total-N, total-P, total-K, cation excharge capacity, exchangeable bases (Ca, Mg, Na dan K), base saturation is more higher compared with the cleaned LCC Mucuna bracteataland; (3) The different level of land slope (%) has  the different soil pH, organic-C, total-P, total-K, cation excharge capacity. The more higher of the land slope (%) so soil pH, organic-C, total-P, total-K, cation excharge capacity become lower; And (4) using of Mucuna bracteata, slope level and the interaction between slope level and used of Mucuna bracteatawas not effect toroot dry weight, root volume and root occupy.  Keywords: Mucuna bracteata, land slope and soil chemical properties